2010
DOI: 10.1111/j.1553-2712.2009.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasogastric Aspiration and Lavage in Emergency Department Patients with Hematochezia or Melena Without Hematemesis

Abstract: Objectives: The utility of nasogastric aspiration and lavage in the emergency management of patients with melena or hematochezia without hematemesis is controversial. This evidence-based emergency medicine review evaluates the following question: does nasogastric aspiration and lavage in patients with melena or hematochezia and no hematemesis differentiate an upper from lower source of gastrointestinal (GI) bleeding?Methods: MEDLINE, EMBASE, the Cochrane Library, and other databases were searched. Studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…19 Because of these limitations, and the potential patient discomfort, use of a nasogastric tube remains controversial. [20][21] Before-procedure proton pump inhibitor therapy…”
Section: Nasogastric Tubementioning
confidence: 99%
“…19 Because of these limitations, and the potential patient discomfort, use of a nasogastric tube remains controversial. [20][21] Before-procedure proton pump inhibitor therapy…”
Section: Nasogastric Tubementioning
confidence: 99%
“…Patients with UGIB may also present with hematochezia. Nasogastric lavage may not be a useful procedure if the patients do not have hematemesis [2]. Clinical factors such as the history of alcohol consumption, smoking, or NSAID use were found to be related to UGIB in previous studies [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that it is difficult to clearly identify bilious fluid by visual inspection alone6 and some patients with duodenal ulcers may have a clear NG aspirate 5. Moreover, NG aspiration has a low sensitivity (42–84%) and NPV (0.2–0.62) to rule out an upper gastrointestinal source of bleeding in patients presenting with melena and/or hematochezia without hematemesis 21. In our experience, a careful history and physical examination are superior to NG tube placement for determining the site—upper, small bowel, or lower gastrointestinal tract—of bleeding.…”
Section: Discussionmentioning
confidence: 99%